Cultural interchangeability in humor translation-adaption : a case study of the sitcom modern family. - Estupiñán Criollo, Nadya Lorena (2022)
This research work reports on the extralinguistic (pragmatic-cultural) analysis of a popular American sitcom. Sitcoms contain humor, which is transferred to TL audiences. Cultural adaptation aids in the development of the message intended in the SL. Berger's classification of humor, i.e., the four groups identified, are at work in various contexts. The scope of humor is culturebound. Jokes can be a reflection of the social and cultural context in which they are constructed. Culture is represented by the customary views, social forms, and traits based on race, religion, or social groups within the distinctive features of daily life shared by people in a particular place or time. Culture is illustrated in the TV sitcom Modern Family, which is the subject of study because it depicts the daily interaction of three families from various backgrounds, comprising various beliefs, races, and social forms. The purpose of this study is to provide a thorough analysis of the many types of humor that are widely employed in sitcoms, which will, in turn, aid depiction of the translation process (by means of subtitling) and measure effectiveness in the rendering of jokes.